The Effect of Foot Reflexology on Fatigue, Sleep Quality, Physiological Indices, and Electrocardiogram Changes in Patients with Acute Myocardial Infarction: A Randomized Clinical Trial - Nilofar Pasyar; Masoume Rambod; Zahra Najafian; Mohammad Hossein Nikoo; Amin Kordi Yoosefinejad; Mahdi Salmanpour (Wolters Kluwer Medknow Publications, 2024)
Background: Limited evidence is available regarding the effect of reflexology on Acute Myocardial Infarction (AMI). The present study evaluated the effect of foot reflexology on fatigue, sleep quality, physiological indices, and electrocardiogram changes in AMI. Materials and Methods: This clinical trial was conducted on 80 subjects with AMI. They were divided into an intervention (received reflexology for 3 consecutive days) and a control (received the routine care) group. The Multidimensional Fatigue Inventory, the Pittsburgh Sleep Quality Index, a pain numeric analog scale, a daily physiological indices form, and daily electrocardiogram were used to collect data. The collected data were analyzed in SPSS software. The study was conducted based on CONSORT criteria. Results: After controlling the covariates, a significant difference was found between the intervention and control groups with regard to the mean scores of fatigue (F5,80 = 16.33; p < 0.001), sleep quality (F5,80 = 16.56; p < 0.001), and chest pain intensity (F5,80 = 6.86; p = 0.010); means of systolic blood pressure (F5,80 = 22.20; p < 0.001), heart rate (F5,80 = 5.86; p = 0.010), respiration (F5,80 = 9.37; p = 0.003), and temperature (F5,80= -4.23; p < 0.001); and incidence of ST-segment (χ21,80 = 5.00; p = 0.020) and T-wave changes (χ21,80 = 6.05, p = 0.010) on the fourth day of the intervention. Conclusions: Given the effectiveness of foot reflexology in different aspects of AMI patients, the implementation of this intervention is recommended for these patients in coronary care units.